Playing with color : 50 graphic experiments for exploring color design principles - Mehl, Richard (Playing., 2013)
Playing with Color is a highly accessible, fun approach to learning color application and principles. This hands-on book begins with an introduction to the philosophy of learning through the process of play. It then leads to a series of experimental design projects with an emphasis on color, providing the reader with a "toolkit" of ideas and skills. The awareness and sensitivity to form, color, material and craft gained through these visual experiments will increase the designer's confidence in their personal and professional design work. This book can be used in the classroom or independentl.